Integrated Process Skills Fostering A Cognitive Variable For Problem Solving In Physics Teaching At Secondary Level - Prem S. R., Nithya (International Journal of Psychosocial Rehabilitation, 2020)
The study examines the correlation between problem solving and integrated process skills among secondary students of Kerala. Problem Solving Test and Integrated Process Skills Test were used as tools. The study was designed as a descriptive and normative survey. The sample of 100 students selected at random, from the secondary schools of Kerala. The five integrated process skills considered in the study were identifying variables, formulating hypothesis, defining operationally, interpreting data, and experimenting. The study revealed significant correlation between Problem Solving and Integrated Process Skills among secondary students. The findings of the study imply the need for development of integrated process skills adopting various problem solving strategies to facilitate the cognitive abilities of secondary students.